Application of GIS in urban growth of the city of Pucallpa to management and environmental management - Meza Arquiñigo, Carlos (2011)
Thc srudy is aimcd 10 invcsugarc the urban growlh of thc cicy of Pucallpa (Yarinacocha Callcria and Manaray) through rhe applicar ion 01' Geogral'hic lnforrnation Systcms, ro idc.:ntify optimal arcas foe rhc purpose of ordcring space and propt:r environmcntal managemcnt cnvironrnent. '1herefore: Using CIS, we evaluatcd [he sparial urban devclopmcnt berwccu 1993 and 2010 showing urban growth at a rarc of apprcximarcly 100%, which mcanx ehar each ycar is incrcasing by '5% arca, rhe cause of rhis mercase is duc to popularion growrh as " resulr of migrnrion. The arca of the ciry of Pucallpa has grown over rime, sysrcmarkally rcplacing rural land, natural and scmi-induding wcrlands, hajialcs, pipes - for co\'erage and urban land uses. In addirion, rhere has becn an imporrant process of fragmcnranon of arcas of high cnvironmcnral qualit}· of (he landscapc, locared wirhin and around werlands.